Measurement-based methodology for modelling the energy consumption of mobile devices. (6th February 2020) - Hamzaoui, Khalil Ibrahim; Berrajaa, Mohammed; Azizi, Mostafa; Lipari, Giuseppe; Boulet, Pierre
Energy consumption is the result of interactions between hardware, software, users, and the application environment. Optimisation of energy consumption has become crucial, and energy is considered a critical resource, so it is important to know and understand both how energy is measured and consumed on mobile devices. An accurate knowledge will allow us to develop efficient solutions to reduce energy consumption in order to improve the user experience. In this paper, we propose an experimental methodology to build a model of the energy consumption of mobile applications. Based on precise measurements, we elaborate predictive models of energy consumption for both unconnected and connected applications.